The roles of polysaccharides in tilapia farming: A review - Zulhisyam Abdul Kari; Wendy Wee; Noor Khalidah Abdul Hamid; Mahmoud A.O. Dawood; Nik Nur Azwanida Binti Zakaria; Lee Seong Wei (Aquaculture and Fisheries, 2024)
Impairment of fish growth and immune system due to stress and disease are major constraints in aquaculture industry. Traditionally, antibiotic was used as prophylactic agent in the health management of aquaculture species. However, antibiotic only provide a temporary solution to the problem of disease outbreak. Over-reliance on antibiotic also has led to the increasing cases of antibiotic resistance among pathogenic bacteria from aquaculture sites and contamination of antibiotic residues into human food chain. Probiotic, prebiotic and symbiotic are therefore suggested as alternatives to prophylactic antibiotic to be used in the aquaculture industry. A potential prophylactic agent is polysaccharide that could be developed into an alternative antibiotic for aquatic animals. In this review paper, definition, sources, and mode of action of polysaccharide are presented. The roles of polysaccharides in fish farming with emphasis on growth improvement, immune system enhancement, disease resistance stimulation in tilapia farming, and the effects of polysaccharides on abiotic stressors are summarized and discussed.